A CMOS implementation of controller based all digital phase locked loop (ADPLL). Issue 1 (6th May 2020) - Balikai, Vikas; Kittur, Harish
Abstract : Purpose: Biomedical radio frequency (RF) transceivers require miniaturized forms with long battery life and low power consumption. The medical implant communication service (MICS) band in the frequency range of 402–405 MHz is widely used for medical RF transceivers because the MICS band signals have reasonable propagation characteristics and are suited to achieve good results. The implementation of the RF front-end for medical devices has many challenges as these dictate low power consumption. In particular, phase-locked loop is one of the most critical blocks of the RF front-end. The purpose of this paper is to the design of controller-based all-digital phase-locked loop (ADPLL) in a 45 nm CMOS process. Design/methodology/approach: Initially, an open-loop architecture phase frequency detector (PFD) is designed. Then based on the concept of differential buffer, a differential ring oscillator (RO) is built using capacitive boosting technique. After that, the frequency controller block is built by proper mathematical modeling that does the job of loop filter, which behaves like a phase interpolator. Frequency controller block has tuning register block, tuning word register. The tuning block is built using the Metal Oxide Semiconductor (MOS) caps. Finally, the integration of all the blocks is done and the ADPLL architecture that locks at 402 MHz is achieved. Findings: The designed PFD is dead zone free that operates at 1 GHz. The differential RO oscillates at 495 MHz. The proposed ADPLL operates at 402 MHz with measured phase noise of −98.36 at 1-MHz offset. This ADPLL exhibits rms jitter of 4.626 ps with a total power consumption of 216.5 µW. Research limitations/implications: A time to digital converter (TDC)-less controller-based low power ADPLL covering the MICS frequency band for biomedical applications has been designed in 45 nm/0.68 V CMOS technology. The ADPLL proposed in this draft uses differential oscillator with capacitively boosted technique which reduced the operating voltage to as low as 0.68 V. This ADPLL has a bandwidth of 20 kHz and works at reference frequency of 20 MHz consumed power of 216.5 µW, while generating an output frequency of 402 MHz. The tuning range is from 375 to 428 MHz. With the phase noise of −98.36 dbc/Hz at 1 MHz, a frequency controller block replaces the usage of TDC. Social implications: The designed ADPLL will definitely pave way to greater research arena in the field of biomedical field. This ADPLL is a unique combination that combines electronics and biomedical field. The designed ADPLL is itself a broader application to biomedical field that will have a positive impact on the society. Originality/value: The implementation of open-loop PFD and RO using the capacitive boosting technique is a unique combination. This is comprehended well with frequency controller block that eliminates the usage of TDC and behaves as phase interpolator. The entire design of ADPLL which suits the application of MICS band of frequency has been designed carefully to work at low power.